Peran UNHCR Dalam Menangani Masalah Pengungsi Ethiopia di Sudan tahun 2020-2021 - Lisvia, Lisvia; Aftah, Chairul (Interdependence Journal of International Studies, 2023)
The influx of Ethiopia refugees into Sudan is the result of a civil war involving the Ethiopian federal government and the Tigray political party. The drastic increase in the number of Ethiopian refugees with the condition Sudan is facing an economic cricis has caused Sudan need help from international actors. For this reason, in dealing with Ethiopian refugees the Sudanese government through the CoR invited UNHCR as an international refugee organization to assist Sudan in solving the problem of Ethiopian Refugees.